CHALLENGES IN USING ARTIFICIAL INTELLIGENCE TECHNOLOGIES ІN SMARTPHONE APPLICATIONS - FEDUN, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The rapid proliferation of smartphones has made them indispensable tools, not only for basic communication but also as platforms capable of complex computational tasks. This evolution has opened up new opportunities for deploying Artificial Intelligence (AI) technologies on these devices. However, the integration of AI in smartphone applications is not without challenges. This paper explores the critical issues and constraints associated with implementing AI technologies in mobile environments, particularly focusing on limited hardware resources, data privacy, and ethical considerations. Smartphones are increasingly becoming the primary device for most users, accessing a wide range of personalized applications, thanks to AI. Despite the advantages of enhanced functionality and user experience through AI, several significant limitations exist. These include constrained computational power, high energy consumption, and the need to protect and secure vast amounts of user data. These limitations are critical as they directly impact the effectiveness and viability of AI applications on mobile platforms. The study analyzes various solutions to overcome these challenges, emphasizing the balance between user experience and technological constraints. For instance, localized AI processing on devices can potentially minimize data privacy risks and reduce reliance on continuous internet connectivity. Moreover, advancements in mobile hardware, such as specialized AI processors, are making it feasible to perform sophisticated tasks like natural language processing and real-time image analysis on smartphones themselves. However, the deployment of AI in smartphones raises several ethical and social issues, particularly concerning data privacy and the potential for increased surveillance and data exploitation. The paper discusses the importance of ethical AI frameworks and the need for regulations to safeguard user privacy and ensure the responsible use of AI. In conclusion, while AI can significantly enhance the functionality of smartphone applications, developers and stakeholders must navigate the complex landscape of technical challenges, user expectations, and ethical considerations. Future research should focus on developing more efficient AI algorithms tailored for mobile environments and exploring innovative ways to address the inherent limitations of smartphone hardware.